Web Based Leave Application for Teachers in Rural Multi-Island Regency - Zulkifli, Akhmad; Baharudin (Journal of ICT Applications System, 2024)
The implementation of a web-based leave management system is essential for efficiently handling leave requests for teachers and civil servants in rural, multi-island regency. The existing manual processes are inefficient and prone to delays due to the geographical challenges and resource limitations. This study presents the development of a web-based application using Laravel, PHP, and MySQL to streamline the leave management process. The system allows users to submit, track, and receive notifications about their leave requests in real-time. This paper discusses the system's development, testing, and implementation phases, demonstrating how it significantly reduces administrative burdens and improves efficiency